Maslahah Mursalah al-Ghazali Sebagai Dasar Hukum Fatwa MUI No. 14 Tahun 2020 Tentang Penyelenggaraan Ibadah Dalam Situasi Terjadi Wabah Covid 19 - Risdianto Risdianto (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2021)
During the covid 19 pandemic, the Indonesian Ulema Council issued Fatwa Number 14/2020 concerning the Implementation of Worship in a Covid 19 Outbreak Situation. The contents of the fatwa are, among others, in order to maintain health so as not to be exposed to the corona virus, it is recommended to pray at home only. This is in accordance with the Islamic religion to keep us physically protected from disease. Thus, the MUI Fatwa is in accordance with the principles of the Islamic religion, namely avoiding harm by practicing what is good for human survival. The reason for this MUI Fatwa is known as the mashlahah mursalah which al-Ghazali explains in several of his books. Al-Ghazali stated that mashlahah mursalah is a matter of goodness that is considered by humans which in fact is in accordance with Islamic law.Keywords : Mashlahah Mursalah, al-Ghazali, and Fatwa MUI.